Six-membered NHC stabilized monomeric zinc complexes - Gour, Kritika; Kundu, Gargi; Dash, Soumya Ranjan; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2023)
This paper describes the rare use of a 6-membered saturated N-heterocyclic carbene (NHC) known as 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene (abbreviated as 6-SI-Dipp) as a ligand in zinc chemistry. We report on the investigation of the reactions between 6-SI-Dipp and ZnX2, which resulted in a range of new monomeric 6-SIDipp center dot ZnX2 complexes (X=Et (1), Cl (2), Br (3), and I (4)). We also prepared a new NHC zinc complex where the two substituents of the zinc atom are different, 6-SIDipp center dot Zn(Et)Br (7) through the reaction of the proligand [6-SIDippH]Br with ZnEt2. We have observed that the reactions of complex 1 with sulfur and HBpin led to the removal of the ZnEt2 moiety, resulting in the formation of a C=S double bond and a B H activation product, respectively. Lastly, the reaction of 1 with five-membered NHCs led to the exchange of carbene and the formation of either 5-IDipp center dot ZnEt2 (8) or 5-SIDipp center dot ZnEt2 (9).
Keywords: Lewis adduct; NHC; X-ray diffraction; zinc